Deciphering the Principles of Bacterial Nitrogen Dietary Preferences: a Strategy for Nutrient Containment - Jilong Wang (American Society for Microbiology, 2016)
ABSTRACT A fundamental question in microbial physiology concerns why organisms prefer certain nutrients to others. For example, among different nitrogen sources, ammonium is the preferred nitrogen source, supporting fast growth, whereas alternative nitrogen sources, such as certain amino acids, are considered to be poor nitrogen sources, supporting much slower exponential growth. However, the physiological/regulatory logic behind such nitrogen dietary choices remains elusive. In this study, by engineering Escherichia coli, we switched the dietary preferences toward amino acids, with growth rates equivalent to that of the wild-type strain grown on ammonia. However, when the engineered strain was cultured together with wild-type E. coli, this growth advantage was diminished as a consequence of ammonium leakage from the transport-and-catabolism (TC)-enhanced (TCE) cells, which are preferentially utilized by wild-type bacteria. Our results reveal that the nitrogen regulatory (Ntr) system fine tunes the expression of amino acid transport and catabolism components to match the flux through the ammonia assimilation pathway such that essential nutrients are retained, but, as a consequence, the fast growth rate on amino acids is sacrificed. IMPORTANCE Bacteria exhibit different growth rates under various nutrient conditions. These environmentally related behaviors reflect the coordination between metabolism and the underlying regulatory networks. In the present study, we investigated the intertwined nitrogen metabolic and nitrogen regulatory systems to understand the growth differences between rich and poor nitrogen sources. Although maximal growth rate is considered to be evolutionarily advantageous for bacteria (as remarked by François Jacob, who said that the “dream” of every cell is to become two cells), we showed that negative-feedback loops in the regulatory system inhibit growth rates on amino acids. We demonstrated that in the absence of regulatory feedback, amino acids are capable of supporting fast growth rates, but this results in ammonia leaking out from cells as “waste,” benefiting the growth of competitors. These findings provide important insights into the regulatory logic that controls metabolic flux and ensures nutrient containment but consequently sacrifices growth rate.